Reassessment of Mendelian gene pathogenicity using 7,855 cardiomyopathy cases and 60,706 reference samples - Thomson, K; Watkins, H; Farrall, M; Taylor, J; Walsh, R; Ware, J; Funke, B; Woodley, J; McGuire, K; Mazzarotto, F; Blair, E; Seller, A; et al. (Nature Publishing Group: Open Access Hybrid Model Option B, 2016)
Purpose: The accurate interpretation of variation in Mendelian disease genes has lagged behind data generation as sequencing has become increasingly accessible. Ongoing large sequencing efforts present huge interpretive challenges, but also provide an invaluable opportunity to characterize the spectrum and importance of rare variation. Methods: Here we analyze sequence data from 7,855 clinical cardiomyopathy cases and 60,706 ExAC reference samples to better understand genetic variation in a representative autosomal dominant disorder. Results: We show that in some genes previously reported as important causes of a given cardiomyopathy, rare variation is not clinically informative as there is an unacceptably high likelihood of false positive interpretation. By contrast, in other genes, we find that diagnostic laboratories may be overly conservative when assessing variant pathogenicity. Conclusions: We outline improved analytical approaches that evaluate which genes and variant classes are interpretable and propose that these will increase the clinical utility of testing across a range of Mendelian diseases.